PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DAN SIKAP POSITIF MAHASISWA MELALUI PEMBELAJARAN THINK TALK WRITE - Dewi, Muthia; Dailami, Dailami (Smart Education, 2025)
Abstract: This study aims to describe the Improvement of Critical Thinking Skills and Positive Attitudes of Students through Think Talk Write learning. This type of research is Classroom Action Research. In this study will be described through four stages in the form of cycles, namely the Planning, Action, Observation and Reflection stages. The subjects of this study were students of Asahan University while the objects in this study were students' critical thinking skills and positive attitudes through Think Talk Write learning. Data collection used learning outcome tests and observations. The results of the study obtained that the number of scores obtained from the implementation of Learning in cycle 1 in the classroom was categorized as less successful with an average score of 2.4. The number of scores obtained in cycle 2 was categorized as less successful with an average score of 2.6. The number of scores obtained from the implementation of Learning in cycle 3 was categorized as successful with an average score of 3.9. Thus in cycle 3 the implementation of learning was categorized as successful Keywords: Critical Thinking Skills; Positive Attitudes; Think Talk Write Abstrak: Penelitian ini bertujuan untuk mendeskripsikan Peningkatan Kemampuan Berpikir Kritis dan Sikap Positif Mahasiswa melalui pembelajaran Think Talk Write. Jenis Penelitian ini adalah Penelitian Tindakan Kelas. Dalam penelitian ini akan dijabarkan melalui empat tahap berupa siklus yaitu tahap Perencanaan, Tindakan, Observasi dan Refleksi. Subjek penelitian ini merupakan mahasiswa Universitas Asahan sedangkan Objek dalam penelitian ini adalah kemampuan berpikir kritis dan sikap positif mahasiswa melalui pembelajaran Think Talk Write. Pengumpulan data menggunakan tes hasil belajar dan observasi. Hasil penelitian diperoleh bahwa jumlah skor yang diperoleh dari pelaksanaan Pembelajaran pada siklus 1 di kelas dikategorikan kurang berhasil dengan rata-rata skor 2,4. Jumlah skor yang diperoleh pada siklus 2 dikategorikan kurang berhasil dengan rata-rata skor 2,6. Jumlah skor yang diperoleh dari pelaksanaan Pembelajaran pada siklus 3 dikategorikan berhasil dengan rata-rata skor 3,9. Dengan demikian pada siklus 3 pelaksanaan pembelajaran dikategorikan berhasil Kata kunci: Kemampuan Berpikir Kritis, Sikap Positif, Think Talk Write